A Eukaryote without a Mitochondrial Organelle - Karnkowska, Anna; Vacek, Vojtěch; Zubáčová, Zuzana; Treitli, Sebastian C; Petrželková, Romana; Eme, Laura; Novák, Lukáš; Žárský, Vojtěch; Barlow, Lael D; Herman, Emily K; Soukal, Petr; Hroudová, Miluše; et al. (Current biology, 2016)
The presence of mitochondria and related organelles in every studied eukaryote supports the view that mitochondria are essential cellular components. Here, we report the genome sequence of a microbial eukaryote, the oxymonad Monocercomonoides sp., which revealed that this organism lacks all hallmark mitochondrial proteins. Crucially, the mitochondrial iron-sulfur cluster assembly pathway, thought to be conserved in virtually all eukaryotic cells, has been replaced by a cytosolic sulfur mobilization system (SUF) acquired by lateral gene transfer from bacteria. In the context of eukaryotic phylogeny, our data suggest that Monocercomonoides is not primitively amitochondrial but has lost the mitochondrion secondarily. This is the first example of a eukaryote lacking any form of a mitochondrion, demonstrating that this organelle is not absolutely essential for the viability of a eukaryotic cell.
Keywords: Cytosol; Phylogeny; transkriptom; Mitochondria; Transcriptome; mitochondrie; cytosol; biologická evoluce; Biological Evolution; síra; Sulfur; fylogeneze; Oxymonadida